THE IMPACT OF PORNOGRAPHY ON WOMEN’S SEXUAL HEALTH - Perissini, Ana Larissa Marques (2024)
The easy access to pornographic content, in part, provided by the evolution of technology has contributed to consolidating it as a common practice in contemporary society, bringing implications for both men and women sexual health. However, the impact of pornography on women has still been little explored in scientific literature. This article aims to conduct a review of the scientific literature to identify the impact of pornography consumption on female sexual health. For data collection, articles in Portuguese and English were included in such databases as LILACS, IBECS, and Medline, published during the period from 2017 to 2022. 937 studies were found, which, after applying the filters (3 duplicate studies), an initial reading of the titles and abstracts (913 articles excluded) and subsequently reading the full text (12 excluded), resulted in 9 studies for discussion of the results. Researchers identified both positive aspects of pornography consumption, such as personal self-knowledge and educational bias, and negative points were also found, such as like sexual dysfunction, physical and emotional violence and body dissatisfaction. It concluded that there is a need for more scientific research and sexual education campaigns to discuss the benefits and aggravations of pornography, such an issues of self-esteem and violence.